Environmental justice in agricultural systems: An evaluation of success factors and barriers by the example of the Philippine farmer network MASIPAG - Stefanie Glotzbach (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
A twofold challenge arises from the normative aim of environmental justice to the management of agricultural systems: (1) the improvement of food security and livelihood of the rural poor today; (2) the sustenance and enhancement of the long-term productivity and resilience of agricultural systems to future generations. The paper analyzes the success factors and barriers of the Philippine farmer network MASIPAG in simultaneously realizing both objectives - based philosophically on Rawls' 'A Theory of Justice' (1971), conceptually on specific determinants of the relationship between the objectives, and empirically on the results of a comprehensive evaluation of the MASIPAG network.
Keywords: 330; environmental justice; ecosystem services; agriculture; agrobiodiversity; Philippines; Landwirtschaft; Unternehmensnetzwerk; Umweltschutz; Biodiversität; Rawls-Gerechtigkeitstheorie; Philippinen